Anti-inflammatory effect of Euphorbia hirta in an adjuvant-induced arthritic murine model. (April 2014) - Ahmad, Sheikh Fayaz; Attia, Sabry M.; Bakheet, Saleh A.; Ashour, Abdelkader E.; Zoheir, Khairy M. A.; Abd-Allah, Adel R. A.
<x xml:space="preserve">Abstract</x> Despite extensive research into inflammatory diseases to date, no drugs with favourable safety profiles are available for treatment. Euphorbia hirta (E. hirta) is a tree that is locally used as a traditional medicine in Africa and Australia to treat numerous diseases such as hypertension, antipyretic and anti-inflammatory activities. The aim of the present study was to determine the potential anti-arthritic effects of E. hirta in mouse models of adjuvant induced arthritis (AIA). We treated BALB/c mice with (p.o.) E. hirta (25, 50, 100, and 200 mg/kg) daily (13 days) beginning at the onset of AIA. We examined the effect of E. hirta on key mediators of arthritic-inflammation, including pro-inflammatory (IL-2, IFN-γ, and TNF-α) and anti-inflammatory (IL-4 and IL-5) cytokines, T-cell activation markers (CD25/CD69), and co-stimulatory molecules (CD80/CD86). We also examined the inflammatory mediators (PGE2 and LTB4) response. E. hirta-treated mice showed a substantial reduction in the levels of pro-inflammatory cytokines, down regulated cell activation markers and co-stimulatory molecules, and up regulated anti-inflammatory cytokines. E. hirta decreased the levels of inflammatory-mediators in AIA animals. Supplementation with an E. hirta extract may be a promising treatment for arthritic and inflammatory diseases.